Consumo habitacional: interações discursivas na míidia sobre o ato de morar na cidade de São Paulo - Almeida Junior, Guy Pinto de (2020)
This paper has as its theme the discursive media interactions about the Housing Consumption in the city of São Paulo. The city, as well as the act of living, is approached from three points of view: Communication, Consumption and Biopolitics. Therefore, our main objective is to problematize discursive interactions and the production of meanings in journalistic, advertising and institutional discourses, considering the interrelationships between these views. Housing Consumption is the concept we use to understand how the dynamics of consumption are related to the act of living. We understand it as an intersection between home and housing, that is, symbolic and functional aspects. The theoretical and methodological contribution of the French Discourse Analysis (FDA) leads to the analysis of corpora formed by journalistic texts from Folha de S. Paulo (16) and El País Brasil (11); institutional arrangements from the Secretaria de Habitação do Município de São Paulo (6) and the Movimento dos Trabalhadores Sem-Teto (6); and advertising communications from three projects located in the city of São Paulo: Cyrela by Pininfarina, Caminhos da Lapa e All Liberdade, all published between January 1st, 2017 and May 1st, 2019. To understand the production of meanings, we linked FDA to concepts of Right to the City (LEFEBVRE, 2001), Public Life (GEHL and SVARRE, 2018) and Governmentality (FOUCAULT, 2008). As a result, discursive interactions reflect an environment of political and economic dispute. These, which take place in and out of modalities (journalistic, institutional and advertising), presented different meaning productions about Housing Consumption. Thus, we understand that media discourses reflect the ideological and political dispute over the dynamics production and reproduction of space. In all the discursive modalities analyzed, we notice an appreciation of Biopolitics as a guiding element of the speeches, which touch, in greater or lesser intensity. on normative and regulatory arguments to encompass Housing Consumptio